Perceived Constraints of Organic Turmeric Farmers in Kandhamal District of Odisha - Sahoo, Biswajit; Saha, Anindita; Dhakre, Digvijay Singh; Sahoo, Subha Laxmi (Indian Journal of Extension Education, 2022)
The study was conducted in 2019 to know the constraints perceived by the organic turmeric farmers in the Kandhamal District of Odisha. The study considered 7 major dimensions under which 30 constraints were considered; data was suitably analyzed with the help of principal component analysis. The result of these 7 dimensions of constraints is further divided into several components based on Eigenvalue. Under general constraints, 4 components identified with Eigen Value 3.055, 1.871, 1.278, 1.058 sequentially leveled as scarce organic manure, inaccessible microbiological tools, poor resource quality, and water scarcity. In technological constraints, two components with Eigenvalue 2.498 and 1.518 leveled as costly input with poor knowledge support and biotic stress, respectively. In Extension activity constraints, two components were identified: inadequate Training and improper Training, with Eigenvalues 1.115 & 1.032, respectively. In the case of the remaining 4 main areas, organic market constraints, economic constraints, social constraints, and other constraints, only one component was identified with Eigenvalue 4.623, 1.780, 1.506, 1.318, respectively.
Keywords: Biotic stress; Microbiological tool; Organic manure; Principal component analysis; Training